2016
DOI: 10.1002/oby.21564
|View full text |Cite
|
Sign up to set email alerts
|

Increased aerobic capacity reduces susceptibility to acute high‐fat diet‐induced weight gain

Abstract: Objective Aerobic capacity is the most powerful predictor of all-cause mortality in humans; however, its role in the development of obesity and susceptibility for high fat diet (HFD)-induced weight gain is not completely understood. Methods Herein, we utilized a rodent model system of divergent intrinsic aerobic capacity [high capacity running (HCR) and low capacity running (LCR)], to evaluate the role of aerobic fitness on 1-week HFD-induced (45% & 60% kcal) weight gain. Food/energy intake, body composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…This finding is in agreement with the present results and shows that LCR animals have a limited metabolic flexibility, as demonstrated by accumulation of acetylcarnitine, suggesting an impaired capacity for lipid metabolism . As a result, HCR animals display lower weight gain and feeding efficiency, greater brown adipose mass, as well as greater expression of genes involved in the regulation of thermogenesis compared with LCR after only 1 week of high-fat diet exposure. , …”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with the present results and shows that LCR animals have a limited metabolic flexibility, as demonstrated by accumulation of acetylcarnitine, suggesting an impaired capacity for lipid metabolism . As a result, HCR animals display lower weight gain and feeding efficiency, greater brown adipose mass, as well as greater expression of genes involved in the regulation of thermogenesis compared with LCR after only 1 week of high-fat diet exposure. , …”
Section: Discussionsupporting
confidence: 93%
“…Further, we have reported that when HVR rats were fed a WD, increased voluntary running appeared to offset the increased energy consumption noted in these animals, negating any potential greater metabolic dysfunction from energy excess. This result has been observed in other short-term feeding studies looking at rats with increased aerobic capacity consuming a short-term, high-fat diet (22). Metabolic syndrome induced by a high-fat diet in Sprague-Dawley rats is largely reversible with exercise training (23).…”
Section: Discussionsupporting
confidence: 81%
“…However, others have observed an increased food intake in mice with increased liver FAO following the overexpression of CPT-1 [ 39 ]. Our previous findings suggested that the differences in acute HFHS-induced weight gain, body composition changes, and the regulation of food/energy intake are inversely associated with liver tissue PGC1a expression, fatty acid oxidation, and mitochondrial respiratory capacity [ 40 , 41 , 42 ]. To specifically assess the role of liver mitochondrial fatty acid oxidation and respiratory capacity on short-term HFHS-induced changes in energy homeostasis, we utilized a liver-specific, pgc1a heterozygous mouse model that has previously been observed to have excess lipid accumulation, a reduced expression of fatty acid oxidation, and mitochondrial genes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%